Income inequalities in leisure time physical inactivity in northern Sweden: A decomposition analysis ... - Máté Szilcz; Mosquera, Paola A.; Sebastián, Miguel San; Gustafsson, Per E. (Figshare, 2019)
Aims: Increasing income inequalities in leisure time physical inactivity have been reported in the relatively socially equal setting of northern Sweden. The present report seeks to contribute to the literature by exploring the contribution of different factors to the income inequalities in leisure time physical inactivity in northern Sweden. Methods : This study was based on the 2014 Health on Equal Terms survey, distributed in the four northernmost counties of Sweden. The analytical sample consisted of 21,000 respondents aged 16–84. Six thematic groups of explanatory variables were used: demographic variables, socioeconomic factors, material resources, family-, psychosocial conditions and functional limitations. Income inequalities in leisure time physical inactivity were decomposed by Wagstaff-type decomposition analysis. Results : Income inequalities in leisure time physical inactivity were found to be explained to a considerable degree by health-related limitations and unfavourable socioeconomic ...